Pemberdayaan Posyandu Lansia sebagai Sarana Skrining Sindrom Metabolik pada Lansia di Dusun Iroyudan, Kapanewon Pajangan, Bantul, DIY - Ariyanto, Teguh; Mayang Rachma Aninstya; Budiarto, Arief (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
One of the main diseases in the adult population in Indonesia is metabolic disorders. Metabolic syndrome is a group of several metabolic disorders such as central obesity, high blood pressure, glucose intolerance, and abnormal amounts of fat in the blood (dyslipidemia) which can potentially cause various degenerative diseases such as cardiovascular disease, stroke and type 2 diabetes mellitus. Metabolic syndrome in Indonesia still ranks the highest for the state financial burden with such high mortality and morbidity rates. One of the steps commonly used for initial diagnosis and screening for metabolic syndrome is through Community Health Centers (Puskesmas) and Integrated Health Service Posts (Posyandu). This applied research regarding the empowerment of elderly posyandu presents descriptive data regarding the prevalence of metabolic syndrome in Iroyudan District, provides an evaluation of various risk factors related to metabolic syndrome, especially in the elderly population of Iroyudan District, and provides interventions and impacts to increase the screening capacity at elderly posyandu in Iroyudan District. Based on the research results, demographic data was obtained for the elderly in Iroyudan District regarding several metabolic syndrome screening indicators, namely the abdominal circumference indicator (central obesity) with a total of 31.25% in the elderly population with details of elderly women at 45.4% (n=15) and 0 % in elderly men (n=0); total blood pressure (hypertension) indicators were 68.7% in the elderly population with the details of elderly women at 63.6% (n=21) and 80% among elderly men (n=12); and the blood sugar indicator when above 200 mg/dL was a total of 16.6% in the elderly population with the details of elderly women at 18.1% (n=6) and 13.33% among elderly men (n=2). The total prevalence of metabolic syndrome in the elderly population of Iroyudan District was 8.3% (n=4). Based on this research data and results, it is necessary to increase screening and early detection of metabolic syndrome, one of the strategies is by through empowering elderly posyandu by increasing the knowledge and skills of health cadres, ensuring the quantity and quality of health examination tools, as well as increasing the number of health cadres adjusted to the total population.